Composite electrode material based on sodium iron phosphate of triphylite type and method for its preparation and use
Patent Information
- Application Number
- CN202611151184.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-20
AI Technical Summary
鉴于现有技术的上述缺点、不足,本发明提供一种基于磷铁钠矿型磷酸铁钠的复合电极材料及其制备方法和应用,其解决了现有针对磷铁钠矿型磷酸铁钠处理制备的电极材料,其离子/电子传输双重受限,进而影响磷铁钠矿型磷酸铁钠电极材料扩大应用的技术问题
本发明的有益效果是:本发明的基于磷铁钠矿型磷酸铁钠的复合电极材料及其制备方法和应用,其中,基于磷铁钠矿型磷酸铁钠的复合电极材料具有碳包覆NaFePO4/Na3V2(PO4)3复合晶相的复合结构,NaFePO4相与Na3V2(PO4)3相之间形成异质界面,同时NaFePO4和Na3V2(PO4)3的摩尔比为1.4-1.8:1。NaFePO4相与Na3V2(PO4)3相共同构筑形成的异质结构,有效建立了m-NFP连续离子通道,显著提高了m-NFP电极材料的比容量和循环稳定性。复合电极材料的制备方法制备的电极材料结晶性好,无杂相,成本低廉,过程简单易规模化生产。相对于现有技术而言,本发明制备的基于磷铁钠矿型磷酸铁钠的复合电极材料用于钠离子电池正极,具有高容量和较好的循环性能,能够推动磷铁钠矿型磷酸铁钠电极材料应用,具有极大的潜在应用价值。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrode materials technology, and in particular to a composite electrode material based on sodium ferrophosphate of the ferrophosphate type, its preparation method and application. Background Technology
[0002] Against the backdrop of increasingly urgent global demands for energy structure transformation and sustainable development, lithium-ion batteries, while widely used in electric vehicles and electrochemical energy storage, are constrained by the scarcity of lithium resources and potential safety risks in large-scale energy storage scenarios. Sodium-ion batteries, with their similar working principles to lithium-ion batteries and advantages such as abundant sodium resources and low raw material costs, are gradually becoming a research hotspot in the energy storage field.
[0003] Among numerous sodium-ion battery cathode materials, maricite-NaFePO4 (m-NFP) has attracted widespread attention due to its simple synthesis process and ease of large-scale preparation. However, the crystal structure of this material consists of edge-sharing FeO6 octahedra and corner-sharing PO4 tetrahedra, lacking an effective Na+... + The continuous diffusion channels result in extremely low intrinsic electrochemical activity, limiting the transport efficiency of sodium ions and failing to meet the basic requirements of modern batteries for fast charging and discharging, high energy efficiency, high capacity, and long lifespan.
[0004] In recent years, by employing microstructure control strategies such as nanostructuring, amorphization, and lattice doping, m The intrinsic inactivity limitation of NFP is being gradually overcome. Meanwhile, to address the low electronic conductivity of this material, researchers are also combining it with carbon-based materials such as porous carbon, nitrogen-doped carbon fibers, and reduced graphene oxide. Although these modification methods have advanced m... While NFP performance has improved, it still fails to solve the fundamental problem of its dual limitation on ion / electron transport, and therefore is not yet economically viable and feasible for industrial applications. Summary of the Invention
[0005] (a) Technical problems to be solved In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a composite electrode material based on sodium iron phosphate of phosphate rock type, its preparation method and application, which solves the technical problem that the electrode materials prepared by the treatment of sodium iron phosphate of phosphate rock type have dual limitations in ion / electron transport, thus affecting the wide application of sodium iron phosphate of phosphate rock type electrode materials.
[0006] (II) Technical Solution To achieve the above objectives, the main technical solutions adopted by the present invention include: In a first aspect, embodiments of the present invention provide a composite electrode material based on sodium iron phosphate of the phosphate rock type, wherein the composite electrode material has a composite structure of carbon-coated NaFePO4 / Na3V2(PO4)3 composite crystal phase; Among them, the NaFePO4 / Na3V2(PO4)3 composite crystal phase is formed by the in-situ composite of NaFePO4 phase and Na3V2(PO4)3 phase, and a heterogeneous interface is formed between the two phases; The molar ratio of NaFePO4 to Na3V2(PO4)3 is 1.4-1.8:1.
[0007] In a preferred embodiment of the present invention, the molar ratio of NaFePO4 to Na3V2(PO4)3 in the composite electrode material based on sodium iron phosphate of phosphate rock is 1.5-1.7:1.
[0008] In a preferred embodiment of the present invention, the composite electrode material based on sodium iron phosphate of the phosphate rock type has a carbon coating layer that is boron-doped carbon, or boron and nitrogen-doped carbon.
[0009] Nitrogen doping in the carbon coating layer increases defect sites and Coulomb attraction to optimize ion transport, while stabilizing the electrode / electrolyte interface through chemical bonding (such as hydrogen bonding and coordination) and reducing side reactions. Boron doping enhances the graphitization of the carbon layer, constructing a highly conductive network and providing abundant ion transport channels. In other words, nitrogen and boron doping in the carbon coating layer can significantly accelerate Na+ transport. + The transport dynamics.
[0010] Secondly, embodiments of the present invention provide a method for preparing a composite electrode material based on sodium iron phosphate of the phosphate rock type, comprising the following steps: S1. Sodium source, iron source, phosphorus source, vanadium source, carbon source and organic solvent are ball-milled and mixed evenly, and then dried to obtain a premix. S2. In an inert gas atmosphere, the premix is calcined for the first time and for the second time to obtain a composite electrode material based on sodium iron phosphate of the phosphate rock type, wherein the temperature of the first calcination is lower than the temperature of the second calcination.
[0011] Before the second calcination, the material after the first calcination can be compacted before the second calcination. The specific compaction process can be found in existing technology.
[0012] In a preferred embodiment of the present invention, in the preparation method S1, the sodium source is selected from at least one of sodium carbonate, sodium bicarbonate and sodium acetate; the iron source is selected from at least one of ferrous oxalate and ferric phosphate; the phosphorus source is selected from at least one of ammonium dihydrogen phosphate and ferric phosphate; the vanadium source is selected from at least one of ammonium metavanadate and vanadium pentoxide; the carbon source is selected from at least one of citric acid, urea, glucose and sucrose; and the solvent is selected from at least one of anhydrous ethanol and isopropanol.
[0013] In a preferred embodiment of the present invention, in the preparation method S1, the sodium source is sodium carbonate; the iron source is ferrous oxalate; the phosphorus source is ammonium dihydrogen phosphate; and the vanadium source is ammonium metavanadate. The molar ratio of sodium carbonate to ferrous oxalate is 1.4-1.6:1; the molar ratio of sodium carbonate to ammonium dihydrogen phosphate is 0.9-1.1:2; and the molar ratio of ferrous oxalate to ammonium metavanadate is 1.4-1.8:2.
[0014] In a preferred embodiment of the present invention, the preparation method S1 further includes a nitrogen source, or a nitrogen source and a boron source; The nitrogen source is selected from at least one of melamine and urea; the boron source is selected from at least one of sodium tetrafluoroborate and boric acid.
[0015] In a preferred embodiment of the present invention, in the preparation method S1, ball milling is performed for 5-8 hours at a speed of 350-400 rpm.
[0016] In a preferred embodiment of the present invention, in the preparation method S2, the temperature of the first calcination is 300-350℃ and the time is 3-7h; the temperature of the second calcination is 600-650℃ and the time is 10-14h.
[0017] Thirdly, embodiments of the present invention provide the application of the composite electrode material based on sodium iron phosphate of the phosphate rock type in sodium-ion batteries or cathode materials.
[0018] (III) Beneficial Effects The beneficial effects of this invention are as follows: The composite electrode material based on sodium iron phosphate of the phosphate rock type, its preparation method, and its application are as follows: The composite electrode material based on sodium iron phosphate of the phosphate rock type has a composite structure of carbon-coated NaFePO4 / Na3V2(PO4)3 composite crystal phases, with a heterogeneous interface formed between the NaFePO4 phase and the Na3V2(PO4)3 phase, and the molar ratio of NaFePO4 to Na3V2(PO4)3 is 1.4-1.8:1. The heterogeneous structure formed by the NaFePO4 phase and the Na3V2(PO4)3 phase effectively establishes a continuous m-NFP ion channel, significantly improving the specific capacity and cycle stability of the m-NFP electrode material. The electrode material prepared by the method of composite electrode material has good crystallinity, is free of impurities, has low cost, and the process is simple and easy to scale up. Compared with existing technologies, the composite electrode material based on sodium iron phosphate of phosphate rock prepared in this invention has high capacity and good cycle performance when used as the positive electrode of sodium-ion batteries. It can promote the application of sodium iron phosphate of phosphate rock electrode material and has great potential application value.
[0019] Compared to the composite electrode material based on sodium iron phosphate of the phosphate rock type and having a NaFePO4 / Na2FePO4F composite crystal phase in the applicant's previous invention patent application, the sodium iron vanadium phosphate composite electrode material in this invention has a higher working voltage, a higher energy density, and better rate performance, making it more suitable for use in fast-charging power batteries. Attached Figure Description
[0020] Figure 1 This is a high-resolution TEM image of the electrode material prepared in Example 1 of the present invention, wherein b is an enlarged view of the rectangular region in a; Figure 2 The XRD patterns of the electrode materials prepared in the embodiments and comparative examples of this invention are shown below. Figure 3 The XRD refinement results are shown for the electrode material prepared in Example 1 of this invention. Figure 4 The XRD refinement results are shown for the electrode material prepared in Comparative Example 3 of this invention. Figure 5 The XRD refinement results are shown for the electrode material prepared in Comparative Example 4 of this invention. Figure 6 The charge-discharge curve of the electrode material prepared in Example 1 of this invention; Figure 7 The charge-discharge curve of the electrode material prepared in Comparative Example 1 of this invention; Figure 8 The charge-discharge curve of the electrode material prepared in Comparative Example 2 of this invention; Figure 9The charge-discharge curve of the electrode material prepared in Comparative Example 3 of this invention; Figure 10 The charge-discharge curve of the electrode material prepared in Comparative Example 4 of this invention; Figure 11 Cycle performance curves of sodium-ion batteries prepared using electrode materials prepared for embodiments and comparative examples of the present invention. Detailed Implementation
[0021] To better explain and facilitate understanding of the present invention, the present invention will be described in detail below with reference to the accompanying drawings and specific embodiments.
[0022] To better understand the above technical solutions, exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present invention are shown in the drawings, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that the present invention can be understood more clearly and thoroughly, and that the scope of the present invention can be fully conveyed to those skilled in the art.
[0023] Example 1 This embodiment provides a method for preparing a composite electrode material based on sodium iron phosphate of the phosphate rock type. The specific steps are as follows: (1) 0.954 g sodium carbonate, 1.079 g ferrous oxalate dihydrate, 2.07 g ammonium dihydrogen phosphate, 0.85 g citric acid (carbon source), 0.18 g urea (nitrogen source), 0.09 g boric acid (boron source), 0.936 g ammonium metavanadate and 100 ml anhydrous ethanol were placed in a ball mill and ball-milled for 6 h at a speed of 400 rpm. After drying, a premix was obtained; wherein the nitrogen source and the boron source formed a nitrogen and boron doped carbon coating layer with the carbon source. (2) The premix was calcined at 300℃ for 4 h (N2 atmosphere) and then calcined at 600℃ for 12 h (N2 atmosphere) to obtain sodium iron vanadium phosphate composite electrode material, denoted as NF / VP@C.
[0024] See Figure 1 The image shown is a high-resolution TEM image of the NF / VP@C prepared in this embodiment, which clearly shows the lattice fringes corresponding to the NFP (NaFePO4) phase and the NVP (Na3V2(PO4)3) phase, as well as the heterostructure between them.
[0025] Additionally, XRD analysis was performed on the electrode material NF / VP@C prepared in this embodiment; see [link to relevant documentation]. Figure 2As can be seen, in the XRD pattern of the electrode material NF / VP@C prepared in this embodiment, most of the main peaks are consistent with the NaFePO4 (NFP(PDF#01-071-5040)) card, but diffraction peaks corresponding to Na3V2(PO4)3 (NVP(PDF#00-053-0018)) appear at positions of 14.3° and 28.8°. See also Figure 3 The molar ratio of NFP and NVP phases was found to be 3:2 through XRD refinement.
[0026] Comparative Example 1 This comparative example describes a method for preparing an electrode material. The difference between this comparative example and Example 1 is that: (1) Place 0.53g sodium carbonate, 1.80g ferrous oxalate dihydrate, 1.15g ammonium dihydrogen phosphate, 0.35g citric acid, 0.18g urea, 0.09g boric acid and 50ml anhydrous ethanol in a ball mill and ball mill for 6 h at a speed of 400 rpm. After drying, a premix is obtained. The remaining steps are the same; The electrode material prepared in this comparative example is denoted as NFP@C.
[0027] XRD analysis of the electrode material NFP@C was performed, see [link to documentation]. Figure 2 It can be seen that the XRD pattern of NFP@C is consistent with that of NFP (PDF#01-071-5040) card.
[0028] Comparative Example 2 This comparative example describes a method for preparing an electrode material. The difference between this comparative example and Example 1 is that: (1) Place 0.48 g sodium carbonate, 0.7 g ammonium metavanadate, 1.1 g ammonium dihydrogen phosphate, 0.48 g citric acid, 0.18 g urea, 0.09 g boric acid and 100 ml anhydrous ethanol in a ball mill and ball mill for 6 h at a speed of 400 rpm. After drying, a premix is obtained. The remaining steps are the same; The electrode material prepared in this comparative example is denoted as NVP@C.
[0029] XRD analysis of the electrode material NVP@C was performed, see [link to documentation]. Figure 2 It can be seen that the XRD pattern of NVP@C is consistent with that of the NVP (PDF#00-053-0018) card.
[0030] Comparative Example 3 This comparative example describes a method for preparing an electrode material. The difference between this comparative example and Example 1 is that: (1) Place 0.85 g sodium carbonate, 1.25 g ferrous oxalate dihydrate, 1.84 g ammonium dihydrogen phosphate, 0.73 g citric acid, 0.18 g urea, 0.09 g boric acid, 0.70 g ammonium metavanadate and 100 ml anhydrous ethanol in a ball mill and ball mill for 6 h at a speed of 400 rpm. After drying, a premix is obtained. The remaining steps are the same; The electrode material prepared in this comparative example is denoted as NF / VP@C-1.
[0031] XRD analysis of the electrode material NF / VP@C-1 was performed, see [reference needed]. Figure 2 It can be seen that most of the main peaks of the XRD pattern of NF / VP@C-1 are consistent with the NFP (PDF#01-071-5040) card, but diffraction peaks corresponding to NVP (PDF#00-053-0018) appear at positions of 14.3° and 28.8°. Figure 4 XRD refinement revealed that the molar ratio of NFP and NVP was 5:4.
[0032] Comparative Example 4 This comparative example describes a method for preparing an electrode material. The difference between this comparative example and Example 1 is that: (1) 1.10 g sodium carbonate, 0.90 g ferrous oxalate dihydrate, 2.30 g ammonium dihydrogen phosphate, 0.98 g citric acid, 0.18 g urea, 0.09 g boric acid, 1.17 g ammonium metavanadate and 100 ml anhydrous ethanol were placed in a ball mill and ball-milled for 6 h at a speed of 400 rpm. After drying, a premix was obtained. The remaining steps are the same; The electrode material prepared in this comparative example is denoted as NF / VP@C-3.
[0033] XRD analysis of the electrode material NF / VP@C-3 was performed, see [reference]. Figure 2 It can be seen that most of the main peaks of the XRD pattern of NF / VP@C-3 are consistent with the NFP (PDF#01-071-5040) card, but diffraction peaks corresponding to NVP (PDF#00-053-0018) appear at positions of 14.3° and 28.8°, and these diffraction peaks are stronger. Figure 5 XRD refinement revealed that the molar ratio of NFP to NVP was 4:9.
[0034] Application Example 1 In this application example, the sodium iron vanadium phosphate composite electrode material NF / VP@C prepared in Example 1 is used as the positive electrode of a battery: The positive electrode of the CR2025 coin cell is prepared by coating a uniform slurry containing active material (NF / VP@C), acetylene black and PVDF binder (mass ratio 7:2:1) onto an aluminum foil current collector.
[0035] The electrodes were vacuum dried at 110°C for 6 hours and then punched into discs with a diameter of 14 mm. The typical loading of the active material was controlled at approximately 1.5 mg / cm³. -2 The battery was assembled in an argon-filled glove box (Mikrouna Super 1220 / 750, H2O < 1 ppm, O2 < 1 ppm), using a metallic sodium anode, a glass microfiber diaphragm (Whatman), and a 1M NaClO4 / EC:DMC:EMC (volume ratio 1:1:1) electrolyte containing 2 vol.% fluoroethylene carbonate additive.
[0036] Detection Example 1 This test example corresponds to the CR2025 coin cell of Example 1, and the electrochemical performance of the electrode materials prepared in Comparative Examples 1 to 4 are evaluated respectively: First, CR2025 coin cells were assembled using electrode materials (NFP@C, NVP@C, NF / VP@C-1 and NF / VP@C-3) prepared in Comparative Examples 1 to 4. The positive electrode was prepared by coating an aluminum foil current collector with a uniform slurry containing four active materials (NFP@C, NVP@C, NF / VP@C-1 or NF / VP@C-3), acetylene black and PVDF binder (mass ratio 7:2:1).
[0037] The electrodes were vacuum dried at 110°C for 6 hours and then punched into discs with a diameter of 14 mm. The typical loading of the active material was controlled at approximately 1.5 mg / cm³. -2 The battery was assembled in an argon-filled glove box (Mikrouna Super 1220 / 750, H2O < 1 ppm, O2 < 1 ppm), using a metallic sodium anode, a glass microfiber diaphragm (Whatman), and a 1M NaClO4 / EC:DMC:EMC (volume ratio 1:1:1) electrolyte containing 2 vol.% fluoroethylene carbonate additive.
[0038] The coin cells corresponding to Example 1 and Comparative Examples 1 to 4, using five electrode materials (NF / VP@C, NFP@C, NVP@C, NF / VP@C-1, and NF / VP@C-3), were subjected to charge-discharge tests. The test results are as follows: like Figure 6 As shown, a sodium-ion battery containing NF / VP@C electrode material performs at 0.1C (1 C = 155 mAh g⁻¹). -1Charge-discharge tests were conducted at a current density of [value missing], and the highest specific capacity was observed during the first discharge cycle, reaching 130.3 mAh g⁻¹. -1 See the corresponding cycle performance curves for sodium-ion batteries. Figure 11 .
[0039] like Figure 7 As shown, a sodium-ion battery containing NFP@C performs at 0.1C (1 C = 155 mAh g⁻¹). -1 Charge-discharge tests were conducted at a current density of [value missing], and the first discharge specific capacity was only 51.2 mAh g. -1 See the corresponding cycle performance curves for sodium-ion batteries. Figure 11 .
[0040] like Figure 8 As shown, a sodium-ion battery containing NVP@C performs at 0.1C (1 C = 155 mAh g⁻¹). -1 Charge-discharge tests were conducted at a current density of [value missing], and the first discharge specific capacity was 144.4 mAh g. -1 .
[0041] like Figure 9 As shown, a sodium-ion battery containing NF / VP@C-1 performs at 0.1C (1 C = 155 mAh g⁻¹). -1 Charge-discharge tests were conducted at a current density of [value missing], and the first discharge specific capacity was 117.8 mAh g. -1 .
[0042] like Figure 10 As shown, a sodium-ion battery containing NF / VP@C-3, at 0.1C (1 C = 155 mAh g⁻¹), -1 Charge-discharge tests were conducted at a current density of [value missing], and the first discharge specific capacity was 134.6 mAh g. -1 .
[0043] For the cycle performance curves of the above five types of sodium-ion batteries, please refer to [link / reference]. Figure 11 .
[0044] The above test cases are analyzed as follows: Example 1, as the preferred embodiment, shows that the NF / VP@C electrode material prepared in this example has a molar ratio of NFP to NVP of 3:2, exhibiting the best electrochemical performance (130.3 mAh g⁻¹). -1 The conductivity was significantly higher than that of the pure-phase material prepared in Comparative Example 1. This indicates that the heterogeneous interface formed between NFP and NVP effectively improves the electronic conductivity and sodium ion transport kinetics of the material.
[0045] Comparing the electrode materials prepared in Example 1 with those prepared in Comparative Examples 3 and 4, it can be seen that although the NF / VP@C-3 electrode material prepared in Comparative Example 4 exhibits good first-cycle discharge specific capacity, its capacity retention during cycling is poor. The NF / VP@C-1 electrode material prepared in Comparative Example 3 has a significantly lower first-cycle discharge specific capacity than that of Example 1, and its cycling performance is also significantly lower. This indicates that during the electrode material preparation process, the ammonium metavanadate content affects the ratio of NFP and NVP phases in the electrode material, thereby affecting the discharge specific capacity and battery cycling performance. This is because excessive NVP phase disrupts the optimal heterostructure balance, or excessive vanadium doping negatively impacts the material structure, leading to poor cycling stability.
[0046] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
[0047] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0048] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0049] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0050] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, for example, sequentially. For instance, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For instance, the method may also include step (c), indicating that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0051] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0052] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
Claims
1. A composite electrode material based on sodium iron phosphate of the phosphate rock type, characterized in that, The composite electrode material has a composite structure of carbon-coated NaFePO4 / Na3V2(PO4)3 composite crystal phase; Among them, the NaFePO4 / Na3V2(PO4)3 composite crystal phase is formed by the in-situ composite of NaFePO4 phase and Na3V2(PO4)3 phase, and a heterogeneous interface is formed between the two phases; The molar ratio of NaFePO4 to Na3V2(PO4)3 is 1.4-1.8:
1.
2. The composite electrode material based on sodium iron phosphate of ferrophosphate type as described in claim 1, characterized in that, The molar ratio of NaFePO4 to Na3V2(PO4)3 is 1.5-1.7:
1.
3. The composite electrode material based on sodium iron phosphate of ferrophosphate type as described in claim 1, characterized in that, The carbon coating layer is boron-doped carbon, or boron and nitrogen-doped carbon.
4. A method for preparing a composite electrode material based on sodium iron phosphate of the phosphate rock type as described in any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Sodium source, iron source, phosphorus source, vanadium source, carbon source and organic solvent are ball-milled and mixed evenly, and then dried to obtain a premix. S2. In an inert gas atmosphere, the premix is calcined for the first time and then for the second time to obtain a composite electrode material based on sodium iron phosphate of the phosphate rock type, wherein the temperature of the first calcination is lower than the temperature of the second calcination.
5. The preparation method according to claim 4, characterized in that, In S1, the sodium source is selected from at least one of sodium carbonate, sodium bicarbonate, and sodium acetate; the iron source is selected from at least one of ferrous oxalate and ferric phosphate; the phosphorus source is selected from at least one of ammonium dihydrogen phosphate and ferric phosphate; the vanadium source is selected from at least one of ammonium metavanadate and vanadium pentoxide; the carbon source is selected from at least one of citric acid, urea, glucose, and sucrose; and the solvent is selected from at least one of anhydrous ethanol and isopropanol.
6. The preparation method according to claim 5, characterized in that, In S1, the sodium source is sodium carbonate; the iron source is ferrous oxalate; the phosphorus source is ammonium dihydrogen phosphate; and the vanadium source is ammonium metavanadate. The molar ratio of sodium carbonate to ferrous oxalate is 1.4-1.6:1; the molar ratio of sodium carbonate to ammonium dihydrogen phosphate is 0.9-1.1:2; and the molar ratio of ferrous oxalate to ammonium metavanadate is 1.4-1.8:
2.
7. The preparation method according to claim 4, characterized in that, S1 also includes a nitrogen source, or a nitrogen source and a boron source; The nitrogen source is selected from at least one of melamine and urea; the boron source is selected from at least one of sodium tetrafluoroborate and boric acid.
8. The preparation method according to claim 4, characterized in that, In S1, during ball milling, the ball milling time is 5-8 hours and the rotation speed is 350-400 rpm.
9. The preparation method according to claim 4, characterized in that, In S2, the first calcination temperature is 300-350℃ and the time is 3-7 h; the second calcination temperature is 600-650℃ and the time is 10-14 h.
10. The composite electrode material based on sodium iron phosphate of phosphate rock as described in any one of claims 1 to 3, and its application in sodium-ion batteries or cathode materials.